Arqueoturismo e arte rupestre no semi-árido sergipano: uma análise sob o viés da sustentabilidade - Santos, Jenilton Ferreira (2007)
The development of the archaeological research in Brazil has been showing a rich cultural patrimony. In northern, specifically, the rocky art sites have started to be aim of a disordered touristy exploration, inducing impacts to the cultural patrimony. The archaeotouristical enterprise structured to offer to the tourist a perfect apprehending of the archaeological information and make possible the conservation of the their mines are exceptional. However, this study aim to analysis the trails of touristy exploration of the rocky art sites of the Mundo Novo farm, in Canindé do São Francisco/SE, focusing the structuring process, socioeconomic aspects of the enterprise and the state of conservation of the rocky art. The research was instrumented through analyze of the structuring process by Xingó Archaeology Museum, of the interviews and of the observation and monitoring of the degradation agents in field. About socioeconomic aspects, the archaeotourism has been enterprised in Mundo Novo farm was not planned to unchain the involvement of the community work, disabling the creation of strategic projects of environmental and patrimonial education, not constituting like this an opportunity of generation of local development. The structures constructed to access the sites have serious problems of conservation and were not consolidated, for this reason they are not serve to the minimum functional principles. All that state of conservation of the rocky art, was possible detect and delimit in the pictures several mechanisms of degradation. The interferences detected in the sites are predominantly naturals, with prominence to the problems connected with the erosion of the rocky support. Although, about the action of the termites was possible check that the antrophic action aggravate the problem, proliferate it in areas of the archaeological site. In front of results of this research, we believe that the circuit of the visiting made to the Mundo Novo farm needs to be re-structured, furthermore heal the problems that are unchaining the degradation of the archeological sites.